Effect of position and alteration in synergist muscle force contribution on hip forces when performing hip strengthening exercises - Lewis, C. L.; Sahrmann, S. A.; Moran, D. W. (Clinical Biomechanics, 2008)
Understanding the magnitude and direction of joint forces generated by hip strengthening exercises is essential for appropriate prescription and modification of these exercises. The purpose of this study was to evaluate hip joint forces created across a range of hip flexion and extension angles during two hip strengthening exercises: prone hip extension and supine hip flexion.